2001
DOI: 10.1128/cdli.8.3.571-578.2001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Synthetic Peptides Derived from the Antigens ESAT-6 and CFP-10 for Differential Diagnosis of Bovine Tuberculosis in Cattle

Abstract: In Great Britain an independent scientific review for the government has concluded that the development of a cattle vaccine against Mycobacterium bovis infection holds the best long-term prospect for tuberculosis control in British herds. A precondition for vaccination is the development of a complementary diagnostic test to differentiate between vaccinated animals and those infected with M. bovis so that testing and slaughter-based control strategies can continue alongside vaccination. To date bacillus Calmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
201
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(212 citation statements)
references
References 51 publications
8
201
0
3
Order By: Relevance
“…Although whole-blood gamma interferon assays have been developed for diagnostic of bovine tuberculosis 32,33 , and depending on the antigens used, these tests can effectively differentiate vaccinated from infected animals 13,14,16 A key aim of this work was to identify proteins that could be used to generate an immunological reagent that could be used to differentiate M.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although whole-blood gamma interferon assays have been developed for diagnostic of bovine tuberculosis 32,33 , and depending on the antigens used, these tests can effectively differentiate vaccinated from infected animals 13,14,16 A key aim of this work was to identify proteins that could be used to generate an immunological reagent that could be used to differentiate M.…”
Section: Discussionmentioning
confidence: 99%
“…We detected four such antigens in bovine PPD but all of them (MPT64, CFP21, CFP10 and ESAT-6) have previously been investigated as antigens for development of diagnostic tests 13,16,42 capable of differentiating BCG-vaccinated animals from those infected with bovine tuberculosis [13][14][15][16] . Although no novel BCG-absent antigens were detected in the current analysis the fact that the study did pick up nearly all the known M. bovis-specific antigens demonstrates the power of this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ESAT-6 and CFP-10 have shown great promise as immunodiagnostic reagents for TB in humans and cattle (2,5,39,44). It has been shown that combining M. tuberculosis ESAT-6 and CFP-10 in a diagnostic test for infection or exposure to TB could provide the level of specificity and sensitivity necessary to detect exposure to TB (2).…”
Section: Vol 72 2004 B-and T-cell Epitopes Of Cfp-10 3167mentioning
confidence: 99%
“…In an attempt to identify individual antigens in antigenic fractions using a combination of methods, we determined that these stimulant fractions consisted of 85B, TRB-B, MPB70, TPX, CFP10 and ESAT6. 85B (22), ESAT6 (6,23) and MPB70 (24)(25)(26) are well known T-cell-stimulating antigens, while the antigenicity of CFP10 has only recently been demonstrated (23,25,27). These results support the view that low molecular weight proteins such as ESAT6 (6) play an important role in bovine immune responses to M. bovis.…”
Section: Discussionmentioning
confidence: 52%